MONETARY POLICY, INTEREST RATE AND DISCOUNT TO EVALUATE INVESTMENT PROJECTS - Gomero Gonzales, Nicko Alberto (2016)
Private investments depend on a set of variables, including country risk and interest rate. The degree of sensitivity will also depend on how the financial market is organized, which in many cases, such as the Peruvian, has oligopolistic characteristics. In a way, this may generate a series of distortions in the degree of interest rates influence on productive investments.According to the theoretical conception, interest rate depends on the type of monetary policy implemented by the central banks, if it is expansive it must fall, achieving an opposite effect if the position is restrictive. The evidence indicates that the degree of correlation between the primary issue and the interest rate is weak and positive, so that the effects that the monetary authority can achieve is minimal with respect to investments. The opposite is true of the monetary rate that exerts a high influence on interest rates and, therefore, the discount rate used to evaluate investments.